Laminar composites - Staab, George H. (Butterworth-Heinemann, 1999)
Provides students with the theoretical knowledge and practical skills necessary to identify, model, and solve structural analysis problems. This book mirrors the teaching method used in strength of materials courses taught in the first years of an undergraduate degree and relate this higher level treatment back to that.
Keywords: Laminated materials.; Composite materials.; elektronické knihy; electronic books